Target displacements during eye blinks trigger automatic recalibration of gaze direction - Maus, Gerrit W. (2020)
Eye blinks cause disruptions to visual input and are accompanied by rotations of the eyeball [1]. Like every motor action, these eye movements are subject to noise and introduce instabilities in gaze direction across blinks [2]. Accumulating errors across repeated blinks would be debilitating for visual performance. Here, we show that the oculomotor system constantly recalibrates gaze direction during blinks to counteract gaze instability. Observers were instructed to fixate a visual target while gaze direction was recorded and blinks were detected in real time. With every spontaneous blink-while eyelids were closed-the target was displaced laterally by 0.5° (or 1.0°). Most observers reported being unaware of displacements during blinks. After adapting for ∼35 blinks, gaze positions after blinks showed significant biases toward the new target position. Automatic eye movements accompanied each blink, and an aftereffect persisted for a few blinks after target displacements were eliminated. No adaptive gaze shift occurred when blinks were simulated with shutter glasses at random time points or actively triggered by observers, or when target displacements were masked by a distracting stimulus. Visual signals during blinks are suppressed by inhibitory mechanisms [3-6], so that small changes across blinks are generally not noticed [7, 8]. Additionally, target displacements during blinks can trigger automatic gaze recalibration, similar to the well-known saccadic adaptation effect [9-11]. This novel mechanism might be specific to the maintenance of gaze direction across blinks or might depend on a more general oculomotor recalibration mechanism adapting gaze position during intrinsically generated disruptions to visual input.